PELAKSANAAN KURIKULUM 2013 DALAM PEMBELAJARAN PPKn DI SMA AL HUSNA KEDAUNG - Lina Marlina; Siti Khamroh (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
ABSTRACT Implementation of the 2013 curriculum at SMA Al Husna Kedaung in 2015. With the regulation of the minister of education and culture regarding the implementation or implementation of the 2013 curriculum in elementary and senior high schools, the curriculum has been implemented in a many areas. Al Husna Kedaung High School is trying as much as possible in order to make the regulations of the Minister of Education and Culture successful and to realize national goals. (1) To find out the Implementation of the 2013 Curriculum in PPKn Learning at SMA Al Husna Kedaung.(2) To find out what are the teacher's obstacles in implementing 2013 Curriculum in Civics Learning at Al Husna Kedaung High School. (3) To find out the teacher's efforts in overcoming the obstacles to implementing the 2013 curriculum in Civics learning at SMA Al Husna Kedaung. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The data that has been obtained from the research results are processed using qualitative descriptive analysis with primary data as many as 2 PPKn subject teachers at SMA Kedaung. The results of the study on the Implementation of the 2013 Curriculum for Civics in SMA Al Husna Kedaung showed that: (1) Implementation of the 2013 Curriculum for Civics subjects at SMA Al Husna Kedaung had not run effectively because some teachers had not mastered the 2013 curriculum in the form of lesson plans, syllabus, KI- KD, prota, prosem, indicators, learning methods, learning strategies, learning approaches and assessment of learning outcomes. (2) Obstacles experienced by teachers in implementing the 2013 curriculum for Civics subjects at Al Husa Kedaung High School. (3) The efforts made by PPKn teachers in overcoming the obstacles faced in implementing the 2013 curriculum are: Implementation of the 2013 curriculum at Al Husna Kedaung High School, by the 2013 curriculum guidelines.